A Schiff base fluorescence probe for highly selective turn-on recognition of Zn2+. Issue 4 (25th January 2017) - Zhu, Jinli; Zhang, Yuhuan; Chen, Yihan; Sun, Tongming; Tang, Yanfeng; Huang, Yang; Yang, Qingqing; Ma, Danyang; Wang, Yipu; Wang, Miao
Graphical abstract: Highlights: A simple Schiff-based fluorescence sensor for Zn 2+, was synthesized. This sensor was of good selectivity and sensitivity for Zn 2+, especially without the interference of Cd 2+ . This sensor can be used in live cells. Abstract: A simple Schiff baseCTS, synthesized between 2-hydroxy-1-naphthaldehyde and 2-benzylthio-ethanamine, was found to be a good turn-on fluorescence probe for the detection of Zn 2+, due to the restriction of the rotation of the bond between CN and naphthalene ring and/or the blocking of the photo-induced electron transfer (PET) mechanism of the nitrogen atom to naphthalene ring. Excellent selectivity for Zn 2+ was evidenced, over many other competing ions, including Fe 3+, Cr 3+, Ni 2+, Co 2+, Fe 2+, Mn 2+, Ca 2+, Hg 2+, Pb 2+, Cu 2+, Mg 2+, Ba 2+, Cd 2+, Ag +, Li +, K +, and Na +, in EtOH/HEPES buffer (95:5, v/v, pH = 7.4). It was noteworthy that Cd 2+ had no interference with Zn 2+ . The stoichiometric complex ofCTS -Zn 2+ was determined to be 2:1 forCTS and Zn 2+ in molar, based on the Job plot and single crystal X-ray diffraction data. The binding constant of the complex was 85.7 M −2 with a detection limit of 5.03 × 10 −7  M. The fluorescence bio-imaging capability ofCTS to detect Zn 2+ in live cells was also studied. These results indicated thatCTS could serve as a favorable probe for Zn 2+ .